Mutations and karyotype predict treatment response in myelodysplastic syndromes. Issue 11 (30th September 2018) - Idossa, Dame; Lasho, Terra L.; Finke, Christy M.; Ketterling, Rhett P.; Patnaik, Mrinal M.; Pardanani, Animesh; Gangat, Naseema; Tefferi, Ayalew
Abstract: We examined the influence of mutations and karyotype on conventional treatment response, specifically hematological improvement in anemia, in primary myelodysplastic syndromes (MDS). Cytogenetic and next generation sequencing (NGS)‐derived mutation information was available in 357 patients (median age 74 years; 70% males); the revised international prognostic scoring system risk distribution was very high in 11%, high 15%, intermediate 17%, low 40% and very low 16%. At least one mutation was detected in 81% of patients; most frequent were SF3B1 (32%), ASXL1 (27%), TET2 (24%) and U2AF1 (15%). At median follow‐up of 24 months, treatment with hypomethylating agents (HMAs) was documented in 121 (34%) patients, lenalidomide (LEN) in 55 (15%), and erythropoiesis stimulating agents (ESAs) in 136 (38%). ASXL1 mutations adversely affected response to HMAs (27% vs 48%; P  = 0.02) and LEN (9% vs 43%; P  = 0.04), but not ESAs ( P  = 0.6). LEN response was also adversely affected by U2AF1 mutations (0% vs 42%; P  = 0.02) and high risk karyotype (0% vs 41% in intermediate vs 47% in low risk; P  = 0.01). Patients with SF3B1 mutations were more likely to respond to LEN (56% vs 27%; P  = 0.04). Contrary to previous reports, we found no association between TET2 mutations and HMA treatment response (40% vs 41%; P  = 0.9), even in the absence of ASXL1 mutations ( P  = 0.4).We conclude that ASXL1 mutations in MDS predict inferior response to treatment with both HMAs and LEN; response to LEN was also compromised by U2AF1 mutations and high risk karyotype; SF3B1 mutations identified patients likely to respond to LEN.